2021
DOI: 10.1021/acs.jpclett.1c02735
|View full text |Cite
|
Sign up to set email alerts
|

Doorway Mechanism for Electron Attachment Induced DNA Strand Breaks

Abstract: We report a new doorway mechanism for the dissociative electron attachment to genetic materials. The dipole-bound anion acts as the doorway for electron capture in the genetic material. The electron gets subsequently transferred to a sugar-phosphate or sugar-nucleobase bond, leading to their cleavage. The electron transfer is mediated by the mixing of electronic and nuclear degrees of freedom. The cleavage rate of the sugar-phosphate bond is higher than the breaking of the sugar-nucleobase bond, and both proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…DBS has been ubiquitously found in a variety of chemical or biological systems, ranging from the simplest diatomic molecules to the biological systems or molecular complexes. Recent spectroscopic studies have suggested that the DBS could be a primary candidate for the carrier of the diffuse interstellar species and/or the interstellar PAH anions, giving the enormous astrochemical implication. As the size of the dipole-bound orbital is almost identical to the de Broglie wavelength of the incoming electron, the electron attachment to neutral in the frame of DBS is extremely efficient. , In this aspect, it should be noted that the DBS has also long been conceived as the major doorway in the dissociative electron attachment (DEA) process where the slow electron is captured to be followed by the immediate rupture of the specific chemical bond. DEA is ubiquitously found, ranging from chemistry of the small environmentally important oxide species to radiative damages of biological genetic species of DNA/RNA double/single helices. Although the DEA dynamics have been much investigated in some elegant experimental or theoretical studies, the rather direct experimental evidence for the role of the DBS in the DEA has been quite rare to date. It should be noted here that the present work represents the anion chemistry of the isolated (or lightly solvated) systems as the chemistry/physics of the electron dynamics in heavily solvated or bulk medium is expected to be quite different. , The anionic DBS either loses the excess electron by the autodetachment process or undergoes the transformation into the more stable valence bound anion via the radiative and/or nonradiative transitions before it may be followed by the subsequent chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DBS has been ubiquitously found in a variety of chemical or biological systems, ranging from the simplest diatomic molecules to the biological systems or molecular complexes. Recent spectroscopic studies have suggested that the DBS could be a primary candidate for the carrier of the diffuse interstellar species and/or the interstellar PAH anions, giving the enormous astrochemical implication. As the size of the dipole-bound orbital is almost identical to the de Broglie wavelength of the incoming electron, the electron attachment to neutral in the frame of DBS is extremely efficient. , In this aspect, it should be noted that the DBS has also long been conceived as the major doorway in the dissociative electron attachment (DEA) process where the slow electron is captured to be followed by the immediate rupture of the specific chemical bond. DEA is ubiquitously found, ranging from chemistry of the small environmentally important oxide species to radiative damages of biological genetic species of DNA/RNA double/single helices. Although the DEA dynamics have been much investigated in some elegant experimental or theoretical studies, the rather direct experimental evidence for the role of the DBS in the DEA has been quite rare to date. It should be noted here that the present work represents the anion chemistry of the isolated (or lightly solvated) systems as the chemistry/physics of the electron dynamics in heavily solvated or bulk medium is expected to be quite different. , The anionic DBS either loses the excess electron by the autodetachment process or undergoes the transformation into the more stable valence bound anion via the radiative and/or nonradiative transitions before it may be followed by the subsequent chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…16,31 In this aspect, it should be noted that the DBS has also long been conceived as the major doorway in the dissociative electron attachment (DEA) process where the slow electron is captured to be followed by the immediate rupture of the specific chemical bond. [32][33][34][35] DEA is ubiquitously found, ranging from chemistry of the small environmentally important oxide species to radiative damages of biological genetic species such as DNA/RNA double/single helices. [36][37][38][39] Although the DEA dynamics have been much investigated in some elegant experiments, [40][41][42][43][44] the rather direct experimental evidence for the role of the DBS in the DEA has been quite rare to date.…”
mentioning
confidence: 99%
“…82,85 We have recently shown that the formation of a stable valence- bound state can be competitive to the process leading to the C−O bond cleavage. 82 Hence, the formation of a stable anion may cause suppression of sugar-phosphate bond cleavage and associated strand breaking. Since the rate of formation of the valence-bound state from the doorway dipole-bound state in wobble base pairs is slower than that in WC base pairs, the genetic materials containing wobble base pairs may be more prone to damage caused by LEE-induced attachment in the gas phase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…4 The excess electron could be attached to an antibonding orbital to break the covalent bond. [5][6][7] An aqueous environment has an evident effect on the nucleobases and nucleoside damage by low-energy electrons. The experiments revealed that the presence of a few water molecules would suppress the dissociative channel of the nucleobases.…”
Section: Introductionmentioning
confidence: 99%